VISORY BODY IN TACKLING MONEY POLITICS IN THE 2024 SERANG DISTRICT REGIONAL HEAD ELECTION - Risca, Risca Vanesa; hasuri (Ajudikasi : Jurnal Ilmu Hukum, 2024)
This Money Politics exists because of the obsession of leaders elected by the people to have government authority. Because it is contrary to the principles of the election itself, money politics damages democracy. So, this study will look at how Bawaslu's efforts to prevent and handle money politics in the 2024 Regional Head Elections. The urgency of this study is the threat and impact of money politics on society which can damage democracy and integration in general elections. The research method used is normative juridical which is taken through legal library materials. The results of this study are the role and strategy of Bawaslu in preventing money politics, by educating the public about the threats and impacts of money politics, and the conditions of money politics in the Regional Head Elections in Serang Regency. Thus, Bawaslu has an obligation to take preventive measures so that money politics does not occur in the next general election.